1999
DOI: 10.1111/j.1349-7006.1999.tb00739.x
|View full text |Cite
|
Sign up to set email alerts
|

k‐ras Point Mutations in the Supernatants of Pancreatic Juice and Bile Are Reliable for Diagnosis of Pancreas and Biliary Tract Carcinomas Complementary to Cytologic Examination

Abstract: In order to clarify whether DNA analysis for K-ras mutation can be used to diagnose cancers in supernatants of pancreatic juice and bile, samples from 29 cases of pancreatic, biliary tract, gastric, and neuroendocrine carcinomas, 1 malignant lymphoma case, 2 cases of pancreatic adenoma, 9 cases of chronic pancreatitis and 21 other non-cancer cases were examined. Polymerase chain reaction (PCR) products for K-ras gene codons 2 to 97 of exons 1 and 2 were generated with 33/33 (100%) pancreatic juice and 41/41 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Kras mRNA was found by RT-PCR in 89% of ascites supernatants of patients with pancreatic carcinoma. 11 Our study successfully detected mRNA of tumor markers overly expressed in peritoneal washes of pancreatic cancer patients. The level at which to cut off cycle amplification was determined by using a receiver operating characteristic (ROC) curve.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Kras mRNA was found by RT-PCR in 89% of ascites supernatants of patients with pancreatic carcinoma. 11 Our study successfully detected mRNA of tumor markers overly expressed in peritoneal washes of pancreatic cancer patients. The level at which to cut off cycle amplification was determined by using a receiver operating characteristic (ROC) curve.…”
Section: Discussionmentioning
confidence: 81%
“…[7][8][9][10] Detection of Kras mRNA by PCR has been shown to have a sensitivity of 89% in ascites supernatants of patients with pancreatic carcinoma. 11 Carcinoembryonic antigen (CEA) and CK20 have been detected by immunohistochemistry in patients with metastatic pancreatic adenocarcinoma at a sensitivity rate of 92 and 78%, respectively. 12 Likewise, MUC1 and cytokeratin 7 (CK7) have been shown to be positive in 89 and 91% of patients with pancreatic cancer, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…᭹, p53 and K-ras mutant; , p53 mutant only; ᭺, K-ras mutant only; ᭝, p53 and K-ras wild-type al. 6 and the authors 7 of this article found that the incidence of K-ras mutations in PCa was higher in the Sup than the Sed of PJ, suggesting that the Sup of body fluids is useful for genetic analysis. To improve the molecular diagnosis of BTCa, we analyzed gene mutations in DNA extracts not only from the Sed but also from the Sup of bile samples.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, Yamashita et al 6 and the authors 7 of this article found that the incidence of K-ras mutations in pancreatic cancer (PCa) was higher in the supernatant (Sup) than in the sediment (Sed) of pancreatic juice (PJ), suggesting the usefulness of Sup from body fluids for genetic analysis.…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, although K-ras mutations have been observed in human chronic pancreatitis (Yanagisawa et al 1993), p53 mutations were not observed in chronic pancreatitis but were commonly observed in pancreatic cancer (Casey et al 1993). Analysis of K-ras point mutations in pancreatic juice can be a reliable diagnostic indicator of pancreatic and biliary tract carcinomas (Yamashita et al 1999). Abnormalities in DNA mismatch repair genes, such as hMLH1 and hMSH2, are seen in more than 90% of hereditary nonpolyposis colorectal cancers and are believed to constitute an initial abnormality that facilitates mutations in other genes and leads to adenocarcinoma development (Fishel et al 1993;Papadopoulos et al 1994).…”
Section: Discussionmentioning
confidence: 99%